If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -4 + 5X = 32 Reorder the terms: -4 + X + 5X = 32 Combine like terms: X + 5X = 6X -4 + 6X = 32 Solving -4 + 6X = 32 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 6X = 32 + 4 Combine like terms: -4 + 4 = 0 0 + 6X = 32 + 4 6X = 32 + 4 Combine like terms: 32 + 4 = 36 6X = 36 Divide each side by '6'. X = 6 Simplifying X = 6
| 2x^6+8x^5+5x^4+7x^3+13x^2+0x+23=0 | | 4+10n-3=4n+49-2n | | c/9=11 | | cos(a)=-1 | | 3/14=x-2/42 | | 8=2+2j | | y-4.5=1 | | v-2.5=5.5 | | 5(x-3)+4x= | | 8-2k=2 | | 3s-17=-21+7s | | 9.7x=-78.57 | | 4x=3-3x | | -14a^0b^7c^6/6a^-5b^7c | | 25x^3/(-5x) | | 44+r=1 | | 2x+5-7=12-19 | | (x)(4x)=100 | | 21/3=-9x | | -9+y=-10 | | -9x=21/3 | | 10x^2-20x-85=0 | | 2x+5-7=12 | | -24=3(8z-4) | | 8l=64 | | 4sen^2x-4=0 | | 2(x+2)-0.25x-2+0.5= | | 0.4k+0.4-0.02=4.02 | | 4tan(x)+4=4 | | 10x+60=40x-30 | | 81xsquared=4 | | sqrt(2m-3)+2-sqrt(m+7)=0 |